DUKUNGAN KELUARGA DENGAN KEPATUHAN IBU HAMIL TERINFEKSI HIV DALAM MENGONSUMSI ARV - Nengah Runiari; Dewa Made Ruspawan; Putu Meylitha Budyandani (Jurnal Gema Keperawatan, 2018)
This study aims to determine the relationship between family support and adherence to HIV-infected pregnant women in taking ARVs at Mangusada Badung Hospital. The type of research used is correlational with approach cross sectional. The number of samples is 31 people taken by purposive sampling technique. Data collection used family support questionnaires and observation sheets measuring compliance with the method pill counts. The results showed that 15 people (48.4%) pregnant women infected with HIV received good family support, and from 31 respondents most had compliance with the obedient category of 20 people (64.5%). The test results chi-square obtained a p-value of 0,000 (0.05) so that there was a significant relationship between family support and adherence to HIV-infected pregnant women consuming ARVs at Mangusada Badung Hospital.